CO36 | Inhibitor titer at diagnosis and clinical course in acquired hemophilia A: a single-center experience (Bleeding, Thrombosis and Vascular Biology, 2025)
Background and Aims: Acquired hemophilia A (AHA) is a rare autoimmune bleeding disorder caused by neutralizing autoantibodies against factor VIII (FVIII). While the inhibitor titer is central to diagnosis and monitoring, its relationship with clinical severity and treatment outcomes remains controversial. We analyzed the experience of the Hemophilia Center at Padua University Hospital to evaluate the effectiveness of immunosuppressive and hemostatic treatments, and to assess whether baseline inhibitor titer influences clinical complications and time to remission.